Platelet rich plasma releasate promotes proliferation of skeletal muscle cells in association with upregulation of PCNA, cyclins and cyclin dependent kinases. (4th July 2017) - Tsai, Wen-Chung; Yu, Tung-Yang; Lin, Li-Ping; Lin, Miao-Sui; Wu, Yi-Cheng; Liao, Chih-Hao; Pang, Jong-Hwei S.
Abstract: Platelet rich plasma (PRP) contains various cytokines and growth factors which may be beneficial to the healing process of injured muscle. The purpose of this study is to investigate the effect and molecular mechanism of PRP releasate on proliferation of skeletal muscle cells. Skeletal muscle cells intrinsic to Sprague–Dawley rats were treated with PRP releasate. Cell proliferation was evaluated by 3-[4, 5-Dimethylthiazol- 2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay and immunocytochemistry with Ki-67 stain. Flow cytometric analysis was used to evaluate the cell cycle progression. Western blot analysis was used to evaluate the protein expressions of PCNA, cyclin E1, cyclin A2, cyclin B1, cyclin dependent kinase (cdk)1 and cdk2. The results revealed that PRP releasate enhanced proliferation of skeletal muscle cells by shifting cells from G1 phase to S phase and G2/M phases. Ki-67 stain revealed the increase of proliferative capability after PRP releasate treatment. Protein expressions including cyclin A2, cyclin B1, cdk1, cdk2 and PCNA were up-regulated by PRP releasate in a dose-dependent manner. It was concluded that PRP releasate promoted proliferation of skeletal muscle cells in association with the up-regulated protein expressions of PCNA, cyclin A2, cyclin B1, cdk1 and cdk2.